2019
DOI: 10.1007/s10856-019-6281-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biomaterials hydrophobicity and roughness on biofilm development

Abstract: Most hospitalized patients are carriers of biomedical devices. Infections associated with these devices cause great morbidity and mortality, especially in patients in intensive care units. Numerous strategies have been designed to prevent biofilm development on biodevices. However, biofilm formation is a complex process not fully clarified. In the current study, roughness and hydrophobicity of different biomaterials was analyzed to assess their influences on the biofilm formation of four leading etiological ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 35 publications
(37 reference statements)
5
57
0
Order By: Relevance
“…The materials in which the final counts of CFU/mL were slightly higher were polyurethane and silicone that are very hydrophobic. These results are in accordance with other studies [31,32,33,34] that showed the importance of the hydrophobic effect of the biomaterial surface in the initial adhesion, where bacterial adhesion to the less hydrophobic materials were significantly lower than to the more hydrophobic ones (silicone). Higher roughness seems also to exert some effect in bacterial adhesion [31].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The materials in which the final counts of CFU/mL were slightly higher were polyurethane and silicone that are very hydrophobic. These results are in accordance with other studies [31,32,33,34] that showed the importance of the hydrophobic effect of the biomaterial surface in the initial adhesion, where bacterial adhesion to the less hydrophobic materials were significantly lower than to the more hydrophobic ones (silicone). Higher roughness seems also to exert some effect in bacterial adhesion [31].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, disinfection was more effective in titanium and borosilicate with the lowest hydrophobicity. Previous experiments carried out in our laboratory showed a lower ability of microorganisms to form biofilms on these materials [32]. The materials in which the final counts of CFU/mL were slightly higher were polyurethane and silicone that are very hydrophobic.…”
Section: Discussionmentioning
confidence: 93%
“…In opposition, the higher hydrophobicity and roughness of SilRef may have hindered their initial antifouling activity. However, despite several studies reporting a correlation between the surface hydrophobicity and roughness and cell attachment [40,41], there is evidence that the biofilm formation induces changes in the surface properties [42,43]. These findings corroborate the higher antifouling activity of SilRef surfaces during the biofilm maturation stages.…”
Section: Discussionmentioning
confidence: 61%
“…There is an increasing number of patients carrying biomedical devices. Severe infectious diseases associated with their use cause great morbidity and mortality, especially in critically ill people [84]. These types of GO-AgNP nanohybrids have found applications in different areas, as was previously mentioned.…”
Section: Antimicrobial Activity Assessmentmentioning
confidence: 82%